Price Rigidity and the Origins af Aggregate Fluctuations - Ernesto Pasten; Raphael S. Schoenle; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2018)
We document a novel role of heterogeneity in price rigidity: It strongly amplifies the capacity of idiosyncratic shocks to drive aggregate fluctuations. Heterogeneity in price rigidity also completely changes the identity of sectors from which fluctuations originate. We show these results both theoretically and empirically through the lens of a multi-sector model featuring heterogeneous GDP shares, input-output linkages, and idiosyncratic productivity shocks. Quantitatively, we calibrate our model to 341 sectors and find sectoral productivity shocks can give rise to aggregate fluctuations that are half as large as those arising from an aggregate productivity shock. Heterogeneous price rigidity amplifies the aggregate fluctuations by a factor of more than 2 relative to a flexible-price or homogeneous sticky price economy. Hence, idiosyncratic shocks and heterogeneous price rigidity can account for large parts of aggregate fluctuations and there is hope we will not “forever remain ignorant of the fundamental causes of economic fluctuations” (Cochrane (1994)).
Keywords: E31; E32; O40; 330; input-output linkages; nominal price rigidity; idiosyncratic shocks